IMPRENSA E IGREJA CATÓLICA NO INÍCIO DO SÉCULO XX: CONVERGÊNCIAS E DIVERGÊNCIAS - GURGEL, Eduardo Amaral. (2017)
This thesis describes and analyzes the Catholic intellectuals strategies – the clergy and the laity – utilized by three institutions from the Brazilian Catholic press in the beginning of the 20th Century – Center of Good Press – CBI –, Center Dom Vital – CDV – and the Association of the Catholic Journalists – AJC –, in the defense and maintenance of the so-called “Good Press”. In order to do so, there has been research on the aspects of the trajectory of the catholic intellectuals which were decisive for the institution and organization of the catholic press. The constituent process of such institutions from the catholic press has also been analyzed, as well as facts and events crucial for its development. Grounded on bibliographic and documentary research, our trajectory begins in primary sources arranged in rare documents from characters and institutions, stretching to reference works aiming to understand the researched processes. The research has revealed that there are historic gaps on the institutions from the catholic press, specially regarding the Association of the Catholic Journalists. We have concluded that the primacy of some accomplishments in the press area belong to the Catholic Church, even though this fact is not registered anywhere.